2012
DOI: 10.1515/rns.2011.057
|View full text |Cite
|
Sign up to set email alerts
|

At a PI3K crossroads: lessons from flies and rodents

Abstract: PI3K activation is the starting point of signaling pathways relaying on changes in the phosphorylation levels of membrane phosphoinositides. These pathways have been involved in several neuronal processes, including cellular growth and survival, differentiation, neuroprotection, dendritic growing, and synaptic plasticity among others. Recent data from Drosophila and rodents have demonstrated an unexpected role of PI3K controlling synapse number that lead to functional and behavioral effects. In the short-term,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…8B, C; Table 1). Growth effects of PI3K have been demonstrated in interneurons previously and it was proposed that tyrosine kinases other than the dInR could be upstream regulators [45], [63], [70]. Hence, we show that the cell size of DIMM negative neurons can be increased, but not via the dInR.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…8B, C; Table 1). Growth effects of PI3K have been demonstrated in interneurons previously and it was proposed that tyrosine kinases other than the dInR could be upstream regulators [45], [63], [70]. Hence, we show that the cell size of DIMM negative neurons can be increased, but not via the dInR.…”
Section: Resultssupporting
confidence: 63%
“…Since these neurons do not grow in response to dInR expression PI3K could possibly be activated by other upstream elements than the dInR. It has indeed been proposed that PI3K-induced growth of brain interneurons (and synapse formation) could be triggered by tyrosine kinases other than the dInR [45], [63], [70].…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously demonstrated that activation of the PI3K–Akt–GSK3 pathway increases synaptogenesis and spinogenesis and improves learning in mammals and invertebrates (Acebes and Morales, 2012). In this study, we present a quantitative analysis showing that PI3K activation improves a contextual learning process and specifically favors the formation of small, “thin” spines in both rat hippocampus and cell culture.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphatidylinositide-3 kinase (PI3K) dependent signaling participates in the regulation of several fundamental neuronal processes, including neuronal growth, survival and differentiation, formation of dendrites as well as synaptic plasticity [1]. …”
Section: Introductionmentioning
confidence: 99%